2009
DOI: 10.2478/v10111-009-0011-4
|View full text |Cite
|
Sign up to set email alerts
|

Correlations between phenolic compounds in wood and its decay by chosen species of saprotrophic and parasitic fungi

Abstract: Ocena zależności między występowaniem w drewnie substancji o charakterze fenolowym a jego rozkładem przez wybrane gatunki grzybów saprotroficznych i pasożytniczych

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 5 publications
0
1
0
Order By: Relevance
“…As other fungi of this type, it degrades wood to yield brown, cubical cracks easily broken down. Many factors, including microflora or compounds present in wood, contribute to this complex process (Przybył and Żłobińska-Podejma 2000; Song et al 2016; Zarzyński 2009). Shang et al (2013) showed that wood samples decayed by F. betulina lost 57% of dry weight (dw) and 74% of holocellulose after 30 days, whereas the fungus growing on wheat straw causes 65% loss of dw within 98 days of culture (Valášková and Baldrian 2006a).…”
Section: Wood Decaymentioning
confidence: 99%
“…As other fungi of this type, it degrades wood to yield brown, cubical cracks easily broken down. Many factors, including microflora or compounds present in wood, contribute to this complex process (Przybył and Żłobińska-Podejma 2000; Song et al 2016; Zarzyński 2009). Shang et al (2013) showed that wood samples decayed by F. betulina lost 57% of dry weight (dw) and 74% of holocellulose after 30 days, whereas the fungus growing on wheat straw causes 65% loss of dw within 98 days of culture (Valášková and Baldrian 2006a).…”
Section: Wood Decaymentioning
confidence: 99%